The electronic structure and bonding of Acetylene on PdGa(110) - Bechthold, Pablo Ignacio (2015)
We have studied the adsorption of acetylene on the PdGa(110) surface by Density Functional Theory calculation. Our results predict the hollow site is the most stable location for the adsorbate. In this site, both Pd and Ga atoms interact with acetylene. This molecule is bonded with the C-C bond almost parallel to the surface. A small tilt angle of 4.1° is computed. The C atoms present a rehybridization from sp -> sp2. This rehybridization is also present in the bridge site but it is not present in the top configuration, where the C-C-H bond angle is about 160°. We computed the total density of state for the system and also the projection on Pd, Ga, C, and H atoms. These plots show a shift to lower energies on C and H projected states, which is an indication of stabilization after adsorption. At the same time, there is a reduction in the density for the Pd atom directly bonded to the C atom. The crystal orbital overlap population curves show an increase in the C-C overlap population (OP) after adsorption; while, the C2H2 rehybridizes to a near sp2 geometry. The acetylene withdraws charge from the surface indicating a donation-adsorption mechanism. The formation of Pd-C and Ga-C bonds and a decrease in OP for Pd-Pd and Pd-Ga bonds are detected. We also found, in the hollow site, a reduction in the C-C bond stretching vibrational frequency. This is an indication of the significant distortion in the adsorbed molecule. We have also found that the C-C bond breaking is unfavorable and that semihydrogenation is 2.27 eV more stable than C2H2 + H2 in the gas phase.